ANALISIS PENGARUH KEPUASAN KERJA DAN MOTIVASI TERHADAP KINERJA KARYAWAN DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING - Sumarni, Devi (Manajemen & Bisnis Jurnal, 2021)
The drop we will see from internal factors comes from employee performance, by looking at terms of job satisfaction, earned work motivation and employee commitment to Organization in the workplace will have an impact on employee performance, whether performance increases or decreases, Good or bad. The initial investigation of the study revealed that there were problems faced by East Java Forest Security Bureau employees, the problem being a decrease in employee performance. The population of this study was 5 persons and the sample used for the study was 5 persons/employee. This study uses path analysis method. The results of this study show that job satisfaction has a positive and significant impact on employees' job performance, work motivation has a positive and significant impact on employees' work results. employees, organizational commitment has a positive and significant impact on employee job performance, job satisfaction has a positive and significant impact on organizational commitment, motivation work has a positive and significant effect on organizational commitment, job satisfaction has a positive and significant effect on employee performance with organizational commitment being the intermediate and variable motivation at work has a positive and significant effect on employee performance with organizational participation as an intermediate variable